Modulation of the cough reflex by GABAA receptors in the caudal ventral respiratory group of the rabbit - Cinelli, Elenia; Bongianni, Fulvia; Pantaleo, Tito; Mutolo, Donatella (Frontiers in Physiology, 2012)
We have previously shown that the caudal ventral respiratory group (cVRG) is a possible site of action of some antitussive drugs and plays a crucial role in determining both the expiratory and inspiratory components of the cough motor pattern. In addition, it has been reported that medullary expiratory neurons of the cVRG are subject to potent GABAergic gain modulation. This study was devoted to investigate the role of cVRG GABAA receptors in the control of baseline respiratory activity and cough responses to mechanical and chemical (citric acid) stimulation of the tracheobronchial tree. To this purpose, bilateral microinjections (30-50 nl) of bicuculline or muscimol were performed into the cVRG of pentobarbital sodium-anesthetized, spontaneously breathing rabbits. Bicuculline (1 mM) increased peak abdominal activity and respiratory frequency due to decreases in TE. Cough responses were potentiated mainly owing to increases in the cough number. The recovery was observed within 2 h. On the contrary, muscimol (0.3 mM) abolished abdominal activity and decreased respiratory frequency due to increases in TE. In addition, cough responses were progressively reduced and completely suppressed within 20 min. Partial recovery of cough responses was achieved after 3 h or within 5 min following bicuculline microinjections at the same locations. The sneeze reflex induced by mechanical stimulation of the nasal mucosa persisted following bicuculline and muscimol microinjections. However, the number and intensity of expiratory thrusts were enhanced by bicuculline and suppressed by muscimol. The results provide evidence that a potent GABAA-mediated inhibitory modulation is exerted at the level of the cVRG not only on respiratory activity, but also on cough and sneeze reflex responses.